Non-invasive Cardiac Output Monitoring and Assessment of Fluid Responsiveness in Children With Shock in the Emergency Department - Pranali Awadhare; Radha Patel; Tracy McCallin; Kiran Mainali; Kelly Jackson; Hannah Starke; Utpal Bhalala; Utpal Bhalala; Utpal Bhalala (Frontiers Media S.A., 2022)
IntroductionThe assessment of fluid responsiveness is important in the management of shock but conventional methods of assessing fluid responsiveness are often inaccurate. Our study aims to evaluate changes in objective hemodynamic parameters as measured using electrical cardiometry (ICON® monitor) following the fluid bolus in children presenting with shock and to evaluate whether any specific hemodynamic parameter can best predict fluid responsiveness among children with shock.Materials and MethodsWe conducted a prospective observational study in children presenting with shock to our emergency department between June 2020 and March 2021. We collected the parameters such as heart rate (HR), respiratory rate (RR), systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and hemodynamic data such as cardiac output CO), cardiac index (CI), index of contractility (ICON), stroke volume (SV), stroke index (SI), corrected flow time (FTC), systolic time ratio (STR), variation of index of contractility (VIC), stroke volume variation (SVV), systemic vascular resistance (SVR), and thoracic fluid content (TFC) using the ICON monitor before and after fluid bolus (FB). We assessed percent change (Δ) and used paired-sample Student's t-test to compare pre- and post-hemodynamic data and Mann-Whitney U-test to compare fluid responders and non-responders. P-Values < 0.05 were considered statistically significant.ResultsWe recorded 42 fluid interventions in 40 patients during our study period. The median IQR age was 10.56 (4.8, 14.8) years with male/female ratio (1.2:1). There was a significant decrease in ΔRR [−1.61 (−14.8, 0); p = 0.012], ΔDBP [−5.5 (−14.4, 8); p = 0.027], ΔMAP [−2.2 (−11, 2); p = 0.018], ΔSVR [−5.8 (−20, 5.2); p = 0.025], and ΔSTR [−8.39 (−21, 3); p = 0.001] and significant increase in ΔTFC [6.2 (3.5, 11.4); p = 0.01] following FB. We defined fluid responders by an increase in SV by ≥10% after a single FB of 20 ml/kg crystalloid. Receiver operating curve analysis revealed that among all the parameters, 15% change in ICON had an excellent AUC (0.85) for the fluid responsiveness.ConclusionOur study showed significant changes in objective hemodynamic parameters, such as SVR, STR, and TFC following FB in children presenting with shock. A 15% change in ICON had an excellent predictive performance for the fluid responsiveness among our cohort of pediatric shock.